(X+2y)-(x-3y)i=2

Simple and best practice solution for (X+2y)-(x-3y)i=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+2y)-(x-3y)i=2 equation:


Simplifying
(X + 2y) + -1(x + -3y) * i = 2

Remove parenthesis around (X + 2y)
X + 2y + -1(x + -3y) * i = 2

Reorder the terms for easier multiplication:
X + 2y + -1i(x + -3y) = 2
X + 2y + (x * -1i + -3y * -1i) = 2
X + 2y + (-1ix + 3iy) = 2

Reorder the terms:
X + -1ix + 3iy + 2y = 2

Solving
X + -1ix + 3iy + 2y = 2

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add 'ix' to each side of the equation.
X + -1ix + 3iy + ix + 2y = 2 + ix

Reorder the terms:
X + -1ix + ix + 3iy + 2y = 2 + ix

Combine like terms: -1ix + ix = 0
X + 0 + 3iy + 2y = 2 + ix
X + 3iy + 2y = 2 + ix

Add '-3iy' to each side of the equation.
X + 3iy + -3iy + 2y = 2 + ix + -3iy

Combine like terms: 3iy + -3iy = 0
X + 0 + 2y = 2 + ix + -3iy
X + 2y = 2 + ix + -3iy

Add '-2y' to each side of the equation.
X + 2y + -2y = 2 + ix + -3iy + -2y

Combine like terms: 2y + -2y = 0
X + 0 = 2 + ix + -3iy + -2y
X = 2 + ix + -3iy + -2y

Simplifying
X = 2 + ix + -3iy + -2y

See similar equations:

| X(x-3)(x+1)= | | A-6=77 | | 12x^4+8x^2-20=0 | | 245=x+166 | | -k+5(-3k+3)=15-4K | | P^3-4p^2=O | | w+2=98 | | sen4x=1/2 | | 5+14a=9a-2 | | 15+14p=2 | | 3(-4)=9 | | j-47=29 | | 2x+1+2x=96 | | (8)/(3X^2) | | -3x^2+24x=17 | | 92=x+20 | | y+2.7=18.3 | | 120n=1320 | | 39-3x=7(x+2)-5 | | A-15x=0 | | y=-0.5*2 | | 6a=126 | | 1.25=2x | | X/2=18/x | | 3x-34=2(x-18) | | 2.42 = p2 | | 3(3x-3)=21 | | (X+3)-2X=35+X | | 16(x+2)-4x=4(3x+2)-9 | | 8x+66=3x+31 | | x+46=5x+10 | | 89=1x+100 |

Equations solver categories